Metabolic sensors and their interplay with cell signalling and transcription - Krejčí, Alena (Biochemical Society transactions, 2012)
There is an intimate, yet poorly understood, link between cellular metabolic status, cell signalling and transcription. Central metabolic pathways are under the control of signalling pathways and, vice versa, the cellular metabolic profile influences cell signalling through the incorporation of various metabolic sensors into the signalling networks. Thus information about nutrients availability directly and crucially influences crucial cell decisions. In the present review, I summarize our current knowledge of various metabolic sensors and give some examples of the integration of metabolically derived inputs into the signalling system and the regulation of transcription. I also discuss the Warburg effect where the cross-talk between metabolism and signalling is used to orchestrate rapid cell growth and division. It is becoming clear that future research will concentrate on the collection of small-molecule metabolites, whose concentration fluctuates in response to cellular energy levels, searching for their sensors that connect them to the signalling and transcriptional networks.
Keywords: buňky; genetická transkripce; Transcription, Genetic; Cells; signální transdukce; Signal Transduction; metabolické sítě a dráhy; Energy Metabolism; Animals; Humans; energetický metabolismus; lidé; zvířata; proliferace buněk; Cell Proliferation; Metabolic Networks and Pathways